Translation Teaching in China - Lei, Mu (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractTranslation teaching is a process that translation theories could be applied to widely. In-depth study of how translation is taught can set the course for continuous improvement in translation itself. This paper looks at the present situation of translation teaching in mainland China from the following angles: the history of translation teaching, the importance of translation teaching, teaching materials, teaching methods, research into translation teaching, and teacher training. The paper concludes that the development of translation teaching depends on guidance from translation theory, and that effective translator training must incorporate the research and development of translation teaching theories. Therefore, teachers of translation must pay attention to translation studies as well as translation teaching theories.